2021
DOI: 10.1037/apl0000497
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging age diversity for organizational performance: An intellectual capital perspective.

Abstract: The global trend of increasing workplace age diversity has led to growing research attention to the organizational consequences of age-diverse workforces. Prior research has primarily focused on the statistical relationship between age diversity and organizational performance without empirically probing potential mechanisms underlying this relationship. Adopting an intellectual capital perspective, we posit that age diversity affects organizational performance via human and social capital. Furthermore, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 198 publications
(353 reference statements)
0
59
0
2
Order By: Relevance
“…Obviously, a sound knowledge base that is kept up to date is highly necessary to protect one's employability across the lifespan (Quendler and Lamb, 2016). In line with Li et al (2020), who adopted an intellectual capital perspective, we argue that age-diverse workforces might be of high value for nowadays' working organizations, in case both workers and their employers protect and foster the continuous development of occupational competencies throughout their working life.…”
Section: Outcomes and Implications Of The Test Of The Multi-group Medmentioning
confidence: 62%
“…Obviously, a sound knowledge base that is kept up to date is highly necessary to protect one's employability across the lifespan (Quendler and Lamb, 2016). In line with Li et al (2020), who adopted an intellectual capital perspective, we argue that age-diverse workforces might be of high value for nowadays' working organizations, in case both workers and their employers protect and foster the continuous development of occupational competencies throughout their working life.…”
Section: Outcomes and Implications Of The Test Of The Multi-group Medmentioning
confidence: 62%
“…Such increased age diversity is often celebrated because it is believed to bring about diverse perspectives, ideas, and problem solutions that are critical for organization and team performance. Yet, research has not found a consistent relationship between team age diversity and performance, with different studies finding either positive (De Meulenaere et al, 2016; De Meulenaere & Kunze, 2020; Li et al, 2021), negative (Joshi & Roh, 2009; Jukka, 2021; van Dijk et al, 2012), or nonsignificant relationships (Ali et al, 2014; Bell et al, 2011; Boehm et al, 2014; Schneid et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These inconclusive findings may be better understood from a social categorization perspective (Reicher et al, 2010; Turner et al, 1987), which suggests that diversity on surface‐level or readily detectable, salient social attributes such as age can lead to intergroup biases and negative intergroup relations if and when these differences become salient (van Knippenberg et al, 2004; van Knippenberg & Mell, 2016; van Knippenberg & Schippers, 2007). Supporting this tenet, research has shown that organizational factors such as leadership, diversity climate, and age‐inclusive management weaken the salience of age differences, thereby improving team functioning (Boehm et al, 2014; Li et al, 2021; Scheuer & Loughlin, in press). Despite the informative nature of these studies, they have overlooked the role of team personality in potentially activating or assuaging the salience of age diversity (Guillaume et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The implications of the aging of the global workforce are well-documented [ 1 ]. Along with an on-average older workforce, organizations are experiencing an increase in the age diversity of their workers [ 2 ]. This increased age diversity comes with both opportunities (e.g., encouraging the potential for knowledge sharing at work [ 3 ]) and challenges (e.g., managing employee health to ensure long term employability [ 4 ]).…”
Section: Introductionmentioning
confidence: 99%